2019
DOI: 10.1136/neurintsurg-2019-015371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the dual-layer flow-diverting stent (FRED) for the treatment of intracranial aneurysms

Abstract: PurposeTo describe the efficacy and complications of treating cerebral aneurysms with the Flow Re-direction Endoluminal Device (FRED) and to identify predictors for aneurysm occlusion.MethodsA prospective observational registry including all consecutive aneurysms treated with FRED between December 2015 and July 2018 was designed in one therapeutic neuroangiography department. The primary endpoint for treatment efficacy was complete or near-complete occlusion (O’Kelly–Marotta (OKM) C–D), assessed by three-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…At the 3-month angiographic follow-up, 21 aneurysms (77.7%) showed complete occlusion (OKM score D), and 6 aneurysms showed near-complete occlusion (OKM score C). This rate is comparable with the rates reported in the literature (10,13,17), such as those reported by Pierot et al (28) in the SAFE study, where an adequate occlusion rate of 81.1% was reported using the FRED device. Although the sample size was small, and the follow-up period was short, SV system appear to be a safe and effective form of treatment for unruptured ICA aneurysms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…At the 3-month angiographic follow-up, 21 aneurysms (77.7%) showed complete occlusion (OKM score D), and 6 aneurysms showed near-complete occlusion (OKM score C). This rate is comparable with the rates reported in the literature (10,13,17), such as those reported by Pierot et al (28) in the SAFE study, where an adequate occlusion rate of 81.1% was reported using the FRED device. Although the sample size was small, and the follow-up period was short, SV system appear to be a safe and effective form of treatment for unruptured ICA aneurysms.…”
Section: Discussionsupporting
confidence: 90%
“…Since the Food and Drug Administration (FDA), in 2011, authorized the use of the first Flow diverter (Pipeline Embolization Device, Medtronic, Dublin, Ireland), flow diverters (FDs) began to be used representing an important option in the treatment of large and long brain aneurysms, obtaining satisfactory results both in the degree of occlusion and in the clinical efficacy (1)(2)(3)(4)(5)(6)(7)(8). The neurovascular community has been progressively increasing their use, developing a new-generation the FDs, with different structures, in order to produce better parent artery reconstruction and improve endothelial cells formation across the aneurysm neck (Silk flow diverter, Balt Extrusion, Montmorency, France; FRED, MicroVention, Tustin, CA; Derivo Embolization Device, Acandis GmbH, Germany; Surpass stent, Stryker Neurovascular, Kalamazoo, MI, USA; p64, Phenox GmbH, Bochum, Germany) (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Without losing sight of the fact that these differences exist, it is reassuring to note that the very low 2.8% rate of disabling stroke (mRS score >2) or death seen in this trial is consistently reflected in the other recent major trials of the FRED system, where combined permanent morbidity and mortality was reported as ranging from 2.3% to 4.8%. [9][10][11][12] As was seen with the Pipeline device, 6 13 14 these same studies of the FRED system report improving rates of complete aneurysm occlusion over time, with occlusion at 1 year ranging from 73.3% to 91.3%.…”
Section: Discussionmentioning
confidence: 82%
“…Although the FRED system is a relative newcomer to the flow diversion field, a growing body of high-quality evidence consistently shows it provides satisfactory safety and efficacy results. [9][10][11][12] Some caution must be exercised in comparing the results of these trials as they vary in definitions of adverse safety outcome, the proportion of large versus small aneurysms, proportion of anterior versus posterior aneurysm locations, duration of follow-up, and number of aneurysms concomitantly treated with adjuvant devices such as coils. Additionally, the rate of complete aneurysm occlusion in these trials is generally higher than reported in the current study, perhaps, at least in part, because they did not employ the composite endpoint we used in this study where parent artery occlusion, stenosis >50%, use of adjuvant treatment, or re-treatment of target aneurysm would all be adjudicated as failures of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The data of patients were obtained from a pre-constructed database which was established by the information directly collected by neurologists. The variables of the database included age, gender, mRS [ 34 ], NIHSS [ 35 ], number of aneurysms, aneurysm location, conditions of different aneurysms, aneurysm size, aneurysm morphology and OKM grades [ 34 ] of patient after each surgery.…”
Section: Methodsmentioning
confidence: 99%